Purification and Characterization of Alliinase from Iraqi Garlic (Allium sativum) - Iman Hadi Al-Taai (Journal of Global Pharma Technology, 2016)
The study including purification and characterization of alliinase (EC: 4.4.1.4, Cys sulfoxide lyase, alliin lyase) from Iraqi garlic. Enzyme extraction with sodium phosphate buffer, pH 6.5, the extract was precipitated by addition of an ammonium sulfate with saturation (30-70)%. Gel filtration chromatography was done to purification enzyme by ÄKTA Pure 25 apparatus using superdex 200 column, three peaks were obtained with a good enzyme activity and an enzyme purity were identified by the absence of denaturation substances for protein SDS. Characteristics of pure enzyme showed that optimum pH for an activity was 6 and optimum pH for the stability was between 6-8, while optimum temperature for an activity and the stability were 35°C, 30-45°C respectively. Effect of ions Na, K, Mg+2, Fe+2, Zn+2, and Mn+2 was found stimulate enzymatic reaction while Ca+2, Ni+2, Cu+2 and Hg+2 inhibit the enzymatic reaction. Standard alliin used to determine a value of Km and Vmax and found to be 0.35M and 121.5 µmol/ml/min. respectively. The molecular weight of pure enzyme by electrophoresis technique with the presence of SDS was equal to 49 KDa.Keywords: Alliinase, Alliin lyase, Iraqi garlic, Purification, ÄKTA Pure 25.